Visualizing landmark-based face morphing traces on digital images - Batskos, Ilias; Spreeuwers, Luuk; Veldhuis, Raymond (Frontiers in Computer Science, 2023)
This paper focuses on an identity sharing scheme known as face image morphing or simply morphing. Morphing is the process of creating a composite face image, a morph, by digitally manipulating face images of different individuals, usually two. Under certain circumstances, the composite image looks like both contributors and can be used by one of them (accomplice) to issue an ID document. The other contributor (criminal) can then use the ID document for illegal activities, which is a serious security vulnerability. So far, researchers have focused on automated morphing detection solutions. Our main contribution is the evaluation of the effectiveness and limitations of two image forensics methods in visualizing morphing related traces in digital images. Visualization of morphing traces is important as it can be used as hard evidence in forensic context (i.e., court cases) and lead to the development of morphing algorithm specific feature extraction strategies for automated detection. To evaluate the two methods, we created morphs using two state-of-the-art morphing algorithms, complying with the face image requirements of three currently existing online passport application processes. We found that complementary use of the visualization methods can reveal morphing related traces. We also show how some application process-specific requirements affect visualization results by testing three likely morphing attack scenarios with varied image processing parameters and propose application process amendments that would make forensic image analysis more reliable.